Kontribusi Motivasi Belajar terhadap Kemampuan Menulis Teks Ekposisi - Fitra Afrida Amna; Uli Wahyuni (Jurnal Ilmiah Dikdaya, 2022)
Based on the background of the problem, the purpose of this study is to the contribution of learning motivation on the ability to write text exposition class X SMA N 2 Padang. Quantitative research by using descriptive and correlation design. The study population was all students of class X are divided into nine classes with the number of students 274 people. The sampling technique is done by random sampling that is taking members of the sample population randomized. The total sample is 74 people. The research instrument was a questionnaire and test performance. Techniques to analyze research data using Pearson Product Moment Correlation test (PPM), correlation test, t test, F test, and determinant coefficient formula. Results of this motivation to learn to contribute to the ability to write text exposition of 25.79%. The conclusions of this motivation to learn to contribute and positive relationship significantly the ability to write text exposition.